2020
DOI: 10.3390/mti4030047
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Machine Learning Algorithms to Classify Hand Gestures from Deployable and Breathable Kirigami-Based Electrical Impedance Bracelet

Abstract: Wearable devices are gaining recognition for their use as a biosensor platform. Electrical impedance tomography (EIT) is one of the sensing techniques that utilizes wearable sensors as its primary data acquisition system. It measures the impedance or resistance at the peripheral (skin) level and calculates the conductivity distribution throughout the body. Even though the technology has existed for several decades, modern-day EIT devices are still costly and bulky. The paper proposes a novel low-cost kirigami-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This can lead to any performance outcome purely due to chance. Therefore, as with similar prior work, a 10-fold cross-validation approach was used to reduce the effects of overfitting, and it is suitable for evaluating how the models would work with unseen data [5,36,45,47,83]. We observed that SMO achieved the most consistent classification performance, compared to the other algorithms which tend to exhibit a higher degree of variability.…”
Section: Classificationmentioning
confidence: 80%
“…This can lead to any performance outcome purely due to chance. Therefore, as with similar prior work, a 10-fold cross-validation approach was used to reduce the effects of overfitting, and it is suitable for evaluating how the models would work with unseen data [5,36,45,47,83]. We observed that SMO achieved the most consistent classification performance, compared to the other algorithms which tend to exhibit a higher degree of variability.…”
Section: Classificationmentioning
confidence: 80%
“… The generation, processing, and application of FMG, EMG, and EIT signals. ( a ) Use FMG to predict forces in two directions [ 12 ]; ( b ) a novel kirigami-based bracelet senses the skin impedance signals, which is used to distinguish between different gestures [ 13 ]; ( c ) identify the movement intention based on sEMG [ 14 ]; ( d ) an EIT-based technique for assessing spinal cord injury [ 15 ]. …”
Section: Figurementioning
confidence: 99%
“…Peripheral blood vessel puncture control system based on electrical impedance measurement [ 119 ]. A novel kirigami-based bracelet is used to sense the skin impedance signals for distinguishing between different gestures [ 13 ]. A method based on EMG, MMG, and ultrasound images to study internal muscle morphological changes in stroke survivors while walking [ 120 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation